2015
DOI: 10.1002/ange.201411511
|View full text |Cite
|
Sign up to set email alerts
|

(−)‐Englerin A is a Potent and Selective Activator of TRPC4 and TRPC5 Calcium Channels

Abstract: Current therapies for common types of cancer such as renal cell cancer are often ineffective and unspecific, and novel pharmacological targets and approaches are in high demand. Here we show the unexpected possibility for the rapid and selective killing of renal cancer cells through activation of calcium‐permeable nonselective transient receptor potential canonical (TRPC) calcium channels by the sesquiterpene (−)‐englerin A. This compound was found to be a highly efficient, fast‐acting, potent, selective, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 43 publications
0
52
0
Order By: Relevance
“…Recently, Akbulut et al showed the unexpected possibility for the rapid and selective killing of renal cancer cells (RCCs) through activation of calcium-permeable nonselective transient receptor potential canonical (TRPC) calcium channels by the sesquiterpene (−)-englerin A [1]. This compound was found to be a highly efficient, fast-acting, potent, selective, and direct stimulator of TRPC4 and TRPC5 channels.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Akbulut et al showed the unexpected possibility for the rapid and selective killing of renal cancer cells (RCCs) through activation of calcium-permeable nonselective transient receptor potential canonical (TRPC) calcium channels by the sesquiterpene (−)-englerin A [1]. This compound was found to be a highly efficient, fast-acting, potent, selective, and direct stimulator of TRPC4 and TRPC5 channels.…”
Section: Discussionmentioning
confidence: 97%
“…(−)‐Englerin A ( 1 ) (Figure 1), a guaiane sesquiterpene isolated from the stem bark of the East African plant Phyllanthus engleri by Beutler et al., was found to possess very potent growth inhibitory (GI) activity (GI 50 <20 n M ) against four of eight renal cancer cell lines with approximately 1000‐fold selectivity over most other cancer cell lines in the NCI‐60 panel 1. While the mechanism of action of englerin A remains to be elucidated,2 it has very recently been disclosed that 1 activates transient receptor potential canonical channels 4 and 5 (TRPC4/5) in renal cancer cells to induce cell death caused by Ca 2+ overload 3. Structurally, this molecule features an oxygen‐bridged 5‐6‐5 tricyclic system with seven contiguous stereogenic centers containing a cinnamate side chain at C6 and a glycolate fragment at C9 (englerin numbering).…”
Section: Methodsmentioning
confidence: 99%
“…Noncovalent, lysate-based approaches have been successfully applied to the identification of a wide range of targets, including soluble enzymes such as protein kinases [5], the lipid kinase PIKFyve [11] and many others. However, a number of therapeutically relevant target families, in particular integral membrane proteins such as ion channels and G-protein-coupled receptors, are notoriously incompatible owing to loss of their binding-competent conformation during the experimental workflow [12,13].…”
Section: Affinity-based Approachesmentioning
confidence: 99%